The Influence of Social Media Instagram and Fashion Trends on Consumptive Behavior With Fomo as a Mediator Among Followers of Instagram @SHOPEE_ID - Radja Hadaya Cholifi, Zahran; Pasaribu, Wenni Gretha; Setiowati, Rini (Syntax Corporation, 2026)
This study aims to analyze the influence of Instagram usage and fashion trends on consumptive behavior among @Shopee_id followers, with Fear of Missing Out (FOMO) as a mediating variable. A quantitative research design was employed by collecting data from 383 Instagram followers of @Shopee_id. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The results indicate that Instagram usage and fashion trends significantly influence consumptive behavior, with FOMO acting as a strong mediator. Users who actively engage with fashion content and influencers on Instagram tend to exhibit higher levels of impulsive purchasing behavior driven by FOMO. This study contributes theoretically by developing a framework linking social media usage, fashion trends, and FOMO to consumptive behavior. Methodologically, it strengthens empirical evidence regarding psychological factors in digital consumerism. The findings highlight Instagram’s role in shaping consumer behavior and position FOMO as a critical mediating variable in online fashion purchasing decisions. Practically, the results provide insights for fashion brands and online retailers to leverage trending content and FOMO-based strategies, while also raising awareness of the psychological pressures associated with digital consumption.